Spatial Separation of Cocatalysts on Z‐Scheme Organic/Inorganic Heterostructure Hollow Spheres for Enhanced Photocatalytic H2 Evolution and In‐Depth Analysis of the Charge‐Transfer Mechanism (Adv. Mater. 4/2023). Issue 4 (26th January 2023) - Moon, Hyun Sik; Hsiao, Kai‐Chi; Wu, Ming‐Chung; Yun, Yongju; Hsu, Yung‐Jung; Yong, Kijung
Abstract : Photocatalytic H2 Evolution In article number 2200172, Kijung Yong and co‐workers present a Pt/g‐C3 N4 /TiO2 /IrO x hollow sphere for photocatalytic water splitting. The two cocatalysts, Pt and IrO x, are spatially separated along the Z‐scheme charge‐transfer pathway within the g‐C3 N4 /TiO2 heterojunction. The synergistic effect of the spatial separation of cocatalysts and the Z‐scheme heterojunction boosts charge separation/transfer, leading to superior and stable photocatalytic H2 evolution in water.